If we evaluate at infinity, we have:
![\bf{\displaystyle L = \lim_(x \to \infty){(\log(x^8 - 5))/(x^2)} = (\infty)/(\infty) }](https://img.qammunity.org/2023/formulas/mathematics/high-school/l90g9pgxvir03z2sk0ruce7p1alycg0zr4.png)
However, the infinity of the denominator has a higher order. Therefore, we can conclude that
![\boldsymbol{L = 0.}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7pwwm7f09a477fe6pik3okj1cy8kh88cba.png)
However, proving that the limit is 0 without using L'Hopital or the "order" criterion is complicated. To do so, let us denote:
![\boldsymbol{\displaystyle f(x) = (\log(x^8 - 5))/(x^2) }](https://img.qammunity.org/2023/formulas/mathematics/high-school/u8zh6kp7xnhlfzfw7lnak3p5pxl3n883ob.png)
To find the limit, we must look for two functions h(x) and g(x) such that h(x)≤ f(x)≤ g(x) and
![\boldsymbol{\displaystyle \lim_(x \to \infty){h(x)} = 0, \qquad \lim_(x \to \infty){g(x)} = 0}](https://img.qammunity.org/2023/formulas/mathematics/high-school/h8ggnyb1omrx3q4xhip7e5m0iv1034w3dr.png)
If we find these functions, then we can conclude that
![\bf{\lim_(x \to \infty){f(x)} = 0.}](https://img.qammunity.org/2023/formulas/mathematics/high-school/isnfkjabqgfv48wv9tdb7tzfhetk6adfb9.png)
First, let's note that when x⁸ - 5 > 1, then log(x⁸ - 5) > 0 (and this is true when x is large). Likewise, we have that x² > 0 for x > 0. Therefore, we have:
![\boldsymbol{\displaystyle f(x) = (\log(x^8 - 5))/(x^2) \geq 0}](https://img.qammunity.org/2023/formulas/mathematics/high-school/e3f1txveyg2j2u0bnu8hoxjvxy2xkhk0r3.png)
when x "is big enough". Thus, we have h(x) = 0 where it is clear that
![\bf{\lim_(x \to \infty){h(x)} = 0.}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8vm53wqrt6fynufg2o71x7lx81e7r8sbt3.png)
To find the second function, let's first note that \log is an increasing function, so since x⁸ ≥ x⁸ - 5, then log(x⁸) ≥ log(x⁸ - 5). So we have to
![\boldsymbol{\displaystyle (\log(x^8 - 5))/(x^2) \leq (\log(x^8))/(x^2) }](https://img.qammunity.org/2023/formulas/mathematics/high-school/x3ffh0bcyozezogfxvn0lbamqo68kfg6yd.png)
now, if we take y = e^y, then we can write
![\boldsymbol{\displaystyle (\log(x^8))/(x^2) = (\log(e^(8y)))/(e^(2y)) = (8y)/(e^(2y))}](https://img.qammunity.org/2023/formulas/mathematics/high-school/cslpfjydpstnub92ybc8yxu4raen30o3h4.png)
A very important property about the exponential function is
![\boldsymbol{\displaystyle e^x > (x^n)/(n!)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2z384fynja2iejevytu8cid9p1y53opsj8.png)
For any n
and x > 0. If we take n = 2, then we have
![\boldsymbol{\displaystyle e^(2y) > ((2y)^2)/(2!) = (4y^2)/(2) = 2y^2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/lrflqpveh26c8b723gm57nrtvxku9ylnbi.png)
From this it follows that
![\boldsymbol{\displaystyle (1)/(e^(2y)) < (1)/(2y^2) }](https://img.qammunity.org/2023/formulas/mathematics/high-school/r35rscdbty9r1hjxnswgyxmubr1qvawkyw.png)
Therefore, we have to
![\boldsymbol{\displaystyle (\log(x^8 - 5))/(x^2) \leq (\log(x^8))/(x^2) < (8y)/(2y^2) = (4)/(y) = (4)/(\log x) }](https://img.qammunity.org/2023/formulas/mathematics/high-school/6563wmfitzzpwahv8e4fm0i7qxiwy3wva8.png)
yes,
where
. Also,
. Therefore,
.
![\red{\boxed{\green{\boxed{\boldsymbol{\sf{\purple{Pisces04}}}}}}}](https://img.qammunity.org/2023/formulas/mathematics/high-school/h69oqv9qmaqwnfblcjzijgvjvxebiwy0ws.png)